2017
DOI: 10.1371/journal.pone.0188307
|View full text |Cite
|
Sign up to set email alerts
|

KIR content genotypes associate with carriage of hepatitis B surface antigen, e antigen and HBV viral load in Gambians

Abstract: BackgroundHepatocellular carcinoma (HCC) causes over 800,000 deaths worldwide annually, mainly in low income countries, and incidence is rising rapidly in the developed world with the spread of hepatitis B (HBV) and C (HCV) viruses. Natural Killer (NK) cells protect against viral infections and tumours by killing abnormal cells recognised by Killer-cell Immunoglobulin-like Receptors (KIR). Thus genes and haplotypes encoding these receptors may be important in determining both outcome of initial hepatitis infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In the Gambia, a study showed that carriers of the KIR3DS1 gene were HBV-positive and had a high viral load while KIR2DL3 gene carriers had a low HBV viral load. 33 Genotypes and haplotypes containing more activator genes would play an essential role in chronic infection or elimination of HBV. 47 Combinations of KIR genes and HLA molecules are associated with the development of hepatocellular carcinoma in patients infected with chronic hepatitis B virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Gambia, a study showed that carriers of the KIR3DS1 gene were HBV-positive and had a high viral load while KIR2DL3 gene carriers had a low HBV viral load. 33 Genotypes and haplotypes containing more activator genes would play an essential role in chronic infection or elimination of HBV. 47 Combinations of KIR genes and HLA molecules are associated with the development of hepatocellular carcinoma in patients infected with chronic hepatitis B virus.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Only one study has been conducted in West Africa and showed that Gambian carriers for the KIR3DS1 gene had a high risk of being positive for HBeAg as well as carrying a high HBV viral load, while KIR2DL3 gene carriers had low viral load. 33 In Burkina Faso, there are no reports on the association between the KIR gene frequencies and chronic carriage of HBV. Therefore, our pilot study sought to assess the interplay between the KIR gene frequencies and chronic HBV infection in the population of Burkina Faso and to identify which genes are strongly correlated to the risk of developing CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the functional activity of KIRs and the activating or inhibiting signals which they transmit would be dependent on the KIRs/KIR HLA class I ligands genotype of the individual. Recently, considerable data from case-control studies demonstrate the hypothetical role of KIRs and their HLA ligands as genetic factors involved in viral clearance 4,5,[13][14][15][16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…We earlier demonstrated that KIR/HLA receptor-ligand combinations were associated with chronic liver disease progression and HCC development in HCV-infected patients 16 , 17 . However, no reports have addressed such associations in Japanese patients with HBV to date even though a few studies suggested such associations in other ethnicities 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%